THE EFFECTIVENESS OF THE SIREKAP APPLICATION IN THE 2024 SIDOARJO REGIONAL ELECTIONS AS AN EFFORT TO ENSURE TRANSPARENCY IN VOTE RECAPITULATION RESULTS - Indarwati, Lisya Dwi; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the effectiveness of the SIREKAP application in the implementation of the 2024 Sidoarjo Pilkada in an effort to ensure transparency in the results of the vote recapitulation, and researchers want to examine the results of using the SIREKAP application. Method: Researchers used a descriptive qualitative method, conducting in-depth interviews with specific informants and gathering the information and data needed for the study. They then presented the research findings in the form of descriptive sentences. Results: The results of this study indicate that SIREKAP has been effective in streamlining time, effort, and human resources in the regional elections. However, there are still challenges that can be addressed in the coming period. Improvements such as strengthening the internet network, tightening data security systems, and ensuring data confidentiality will bolster public trust and enhance bureaucratic transparency. Novelty: Villages as the spearhead of policy, this study examines the implementation of the SIREKAP application at polling station 02 in Tanjek Wagir village, Krembung sub-district, Sidoarjo regency. The researchers aimed to assess the application's effectiveness and whether the results achieved the objectives of its creation. They also examined the socialization process prior to the regional elections.